The process of coping with the COVID-19 pandemic from the perspective of nursing professionals (Research, Society and Development, 2021)
Currently the world is experiencing a pandemic caused by the SARS-CoV-2 virus, which forced health services to organize themselves, with municipal health managers, together with regional health managers, being responsible for implementing preventive actions within the scope municipality and the nursing team responsible for carrying out actions. The objective was to understand the process of coping with the COVID-19 pandemic from the perspective of nursing professionals and municipal health managers. It is a qualitative, descriptive and exploratory research, carried out with 17 nursing professionals, through a script of questions. The data were tabulated, organized using the IRaMuTeQ® software and combats. Participants were female, young adults, 12 nurses and five nursing technicians. They perform assistance and coordination activities, and six exercises as two activities concomitantly, and operate at different levels of health care. The study apprehended the feelings and the impact on the personal life of Nursing professionals for being on the front line of COVID-19, the challenges in coping with the disease, as well as the lessons from this process, the transformations in the work process and the role of nursing professionals. COVID-19 changed the processes in health and the lives of nursing professionals.